Epigenetic regulator BMI1 promotes alveolar rhabdomyosarcoma proliferation and constitutes a novel therapeutic target. Issue 8 (27th March 2021) - Shields, Cara E.; Potlapalli, Sindhu; Cuya‐Smith, Selma M.; Chappell, Sarah K.; Chen, Dongdong; Martinez, Daniel; Pogoriler, Jennifer; Rathi, Komal S.; Patel, Shiv A.; Oristian, Kristianne M.; Linardic, Corinne M.; Maris, John M.; et al.
Abstract : Rhabdomyosarcoma (RMS) is an aggressive pediatric soft tissue sarcoma. There are two main subtypes of RMS, alveolar rhabdomyosarcoma (ARMS) and embryonal rhabdomyosarcoma. ARMS typically encompasses fusion‐positive rhabdomyosarcoma, which expresses either PAX3‐FOXO1 or PAX7‐FOXO1 fusion proteins. There are no targeted therapies for ARMS; however, recent studies have begun to illustrate the cooperation between epigenetic proteins and the PAX3‐FOXO1 fusion, indicating that epigenetic proteins may serve as targets in ARMS. Here, we investigate the contribution of BMI1, given the established role of this epigenetic regulator in sustaining aggression in cancer. We determined that BMI1 is expressed across ARMS tumors, patient‐derived xenografts, and cell lines. We depleted BMI1 using RNAi and inhibitors (PTC‐209 and PTC‐028) and found that this leads to a decrease in cell growth/increase in apoptosis in vitro, and delays tumor growth in vivo . Our data suggest that BMI1 inhibition activates the Hippo pathway via phosphorylation of LATS1/2 and subsequent reduction in YAP levels and YAP/TAZ target genes. These results identify BMI1 as a potential therapeutic vulnerability in ARMS and warrant further investigation of BMI1 in ARMS and other sarcomas. Abstract : Treatment of alveolar rhabdomyosarcoma (ARMS) remains a major therapeutic challenge in pediatric oncology. Here, we demonstrate that genetic and pharmacologic inhibition of BMI1 reduces ARMS viability. We show that BMI1 inhibits the tumor suppressive Hippo pathway and, conversely, that BMI1 disruption upregulates Hippo signaling. Collectively, these findings provide an initial framework for targeting BMI1 in ARMS and additional sarcomas.